Exploration of the Potential of 3D-Printed PLA Coated with Hydroxyapatite-Gelatin for Dual Applications in Bone Tissue Engineering and Multi-Layer Cigarette Filters - Nadia Septiana Wulandari; Dyah Hikmawati; Aminatun; Frazna Parastuti (Universitas Airlangga, 2026)
This study investigated the effect of hydroxyapatite–gelatin (HAp–gelatin) coating composition on the physicochemical properties of electrospun-coated 3D-printed polylactic acid (PLA) scaffolds for bone tissue engineering and potential applications as multi-layer cigarette filters. PLA scaffolds were fabricated via Fused Deposition Modelling (FDM) with a rhombitruncated cuboctahedron geometry (strut size: 0.8 mm). Five HAp–gelatin compositions (10:90, 20:80, 30:70, 40:60, and 50:50 %wt) were electrospun at 19 kV, a collector distance of 15 cm, and a flow rate of 0.90 mL/h. The 50:50 formulation failed to produce continuous fibers owing to excessive HAp agglomeration and insufficient gelatin chain entanglement; therefore, only the 10:90–40:60 %wt formulations were characterized by SEM-EDX, FTIR, porosity measurement, water contact angle, and in vitro degradation testing. Electrospinning transformed the smooth PLA surface into a homogeneous nanofibrous layer with fiber diameters of 322.13–469.10 nm. EDX confirmed the presence of C, N, O, P, and Ca, while FTIR verified gelatin amide and HAp phosphate groups without altering the PLA substrate chemistry. Coated scaffolds maintained favorable porosity (58.63–59.19%), exhibited improved hydrophilicity with contact angles decreasing from 90.17° to 59.59–79.41°, and demonstrated controlled degradation behavior over 21 days. Among all formulations, the 40:60 (%wt) HAp–gelatin composition achieved the most balanced performance in fiber homogeneity, hydrophilicity, porosity preservation, and degradation control. The combination of nanoscale fiber architecture, preserved porosity, enhanced wettability, and adsorption-active functional groups makes this formulation the most promising candidate for trabecular bone tissue engineering applications. Furthermore, these physicochemical characteristics indicate potential applicability as a future multi-layer cigarette filter material by facilitating particulate capture and interaction with smoke toxicants. However, direct smoke filtration studies are required to validate filtration performance. Overall, the developed HAp–gelatin coated PLA scaffold demonstrates promising potential for both biomedical and environmental applications.